Morphology and phylogeny of ascomycetes associated with walnut trees (Juglans regia) in Sichuan province, China - Xu, Xiu-Lan; Wang, Fei-Hu; Liu, Chao; Yang, Han-Bo; Zeng, Zhen; Wang, Bao-Xin; Liu, Ying-Gao; Yang, Chun-Lin (Frontiers in Microbiology, 2022)
In Sichuan Province, the walnuts, consisting of Juglans regia, J. sigillata, and the hybrid J. regia × J. sigillata, are commercially important edible nuts, and J. regia is the most widespread plant. To date, the diversity and distribution of fungi inhabiting on Juglans have not received enough attention, although there have been studies focusing on pathogens from fruit and stem. In order to update the checklist of fungi associated with Sichuan walnut, a survey on fungi associating with those three Juglans species from 15 representative regions in Sichuan was conducted. In this paper, ten fungi that distributed in two classes of Ascomycota (Dothideomycetes, Sordariomycetes) were described based on morpho-molecular analyses, of which two novel species Neofusicoccum sichuanense and Sphaerulina juglandina, a known species of Ophiognomonia leptostyla, seven new host or geographical records of Cladosporium tenuissimum, Diatrypella vulgaris, Helminthosporium juglandinum, H. velutinum, Loculosulcatispora hongheensis, Periconia byssoides, and Rhytidhysteron subrufulum are included. Morphological descriptions and illustrations of those fungi are provided.